A high-performance stone plastic floor substrate and preparation method thereof
By optimizing the components and processes of stone plastic floor substrates, combined with recycled marble powder, quartz powder and other materials, the problems of poor mechanical properties and high production costs of existing stone plastic floor substrates are solved, and high performance and low cost stone plastic floor substrate preparation is achieved.
Patent Information
- Application Number
- CN202411876126.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-04
AI Technical Summary
The existing stone plastic floor substrates have poor comprehensive mechanical properties and high production costs.
High-performance stone-plastic floor substrates are used, including recycled marble powder, quartz powder, aluminate coupling agent, polyvinyl chloride resin with moderate polymerization, epoxy soybean oil, calcium zinc composite stabilizer, calcium stearate, acrylonitrile-butadiene-styrene plastic and other components, and the process is optimized to improve performance through a high-speed mixer mixer mixer mixing and extrusion molding.
It improves the strength and toughness of stone plastic floor substrates, enhances impact resistance and shrinkage performance, and reduces production costs. The raw materials used are green and environmentally friendly materials without environmental risks.
Smart Images

Figure CN119750955A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building decoration materials, and in particular to a high-performance stone-plastic floor substrate and a preparation method thereof. Background Art
[0002] Stone plastic board is a new type of building decoration material, which is made of stone powder, PVC resin and other raw materials mixed in a certain proportion. Its core layer is made of stone powder and PVC resin materials, and the surface is covered with a wear-resistant layer and a decorative layer. If it is used as a floor material, an anti-slip layer is added to the bottom layer. It is widely used in building decoration, home decoration, advertising production, garden environment, public space and other fields.
[0003] However, the existing stone plastic floor substrate has the following disadvantages:
[0004] 1. Poor comprehensive mechanical properties;
[0005] 2. High production cost.
[0006] In view of the above, the present invention is proposed. Summary of the invention
[0007] The present invention provides a high-performance stone plastic floor substrate and a preparation method thereof, aiming to improve at least one of the above technical problems.
[0008] In order to solve the above technical problems, the present invention provides a high-performance stone plastic floor substrate, characterized in that it comprises the following components in parts by weight:
[0009] 300-400 parts of filler; 1-5 parts of coupling agent; 100 parts of PVC resin raw material; 5-15 parts of plasticizer; 5-15 parts of heat stabilizer; 0.2-2 parts of lubricant; 5-15 parts of heat stabilizer; 10-20 parts of modifier; wherein the filler includes recycled marble powder and quartz powder.
[0010] As a further optimization, the coupling agent is an aluminate coupling agent.
[0011] As a further optimization, the PVC resin raw material consists of polyvinyl chloride resin with a degree of polymerization of 1250 to 981.
[0012] As a further optimization, the plasticizer is compounded from epoxidized soybean oil and dioctyl terephthalate.
[0013] As a further optimization, the heat stabilizer is a calcium-zinc composite stabilizer.
[0014] As a further optimization, the lubricant is at least one of calcium stearate, polyethylene wax and stearic acid.
[0015] As a further optimization, the modifier is compounded from two of acrylonitrile-butadiene-styrene plastic, chlorinated polyethylene and nitrile rubber.
[0016] The present invention also provides a method for preparing a high-performance stone plastic floor substrate as described above, comprising the following steps:
[0017] Step S1, mixing: pouring recycled marble powder, quartz powder, coupling agent, PVC resin raw material, plasticizer, heat stabilizer, lubricant, and modifier into a high-speed mixer in the order of powder first and liquid second to obtain a substrate board material;
[0018] Step S2, extrusion: extruding the substrate plate material into a mold through an extruder to obtain a semi-finished substrate plate;
[0019] Step S3, cooling and cutting: placing the semi-finished substrate sheet on a cooling device to cool and shape it, and then cutting and trimming the edges to obtain a formed product.
[0020] As a further optimization, step S1 specifically includes:
[0021] Step S11, surface modification: mixing the regenerated marble powder and the coupling agent at 100-110° C. in a high-speed mixer for 30 minutes to obtain modified regenerated marble powder;
[0022] Step S12, cooling: adding the modified regenerated marble powder into a low-speed mixer for cooling, and stirring until the temperature reaches room temperature;
[0023] Step S13, mixing: adding the modified regenerated marble powder cooled in step S12, quartz powder, PVC resin raw material, plasticizer, heat stabilizer, lubricant, and modifier into a high-speed mixer in the order of powder first and liquid later, mixing and drying to obtain a substrate board material.
[0024] As a further optimization, six temperature control zones are provided on the extruder in step S2, and the six temperature control zones are zone 1, zone 2, zone 3, zone 4, zone 5, and zone 6; wherein the temperature setting value of zone 1 is 150-155°C, the temperature setting value of zone 2 is 155-160°C, the temperature setting value of zone 3 is 160-170°C, the temperature setting value of zone 4 is 170-180°C, the temperature setting value of zone 5 is 180-190°C, and the temperature setting value of zone 6 is 180-190°C;
[0025] The mold temperature in step S2 is 190-200°C.
[0026] By adopting the above technical solution, the present invention can achieve the following technical effects:
[0027] The present application provides a high-performance stone plastic floor substrate and a preparation method thereof, wherein PVC resin and recycled marble waste powder modified by a coupling agent are combined with a processing aid of a certain weight ratio, mixed by a high-speed mixer, and processed to obtain a stone plastic floor substrate. The obtained substrate has high strength and a certain toughness, making it not easy to break, having good impact resistance and excellent shrinkage performance, and the raw materials used are also green and environmentally friendly materials, without environmental risks, and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 This is a flow chart of a method for preparing a high-performance stone plastic floor substrate of the present invention;
[0030] Figure 2 It is a schematic flow chart of specific steps in step S1, mixing of the present invention. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the invention claimed for protection, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0032] Depend on Figure 1 to Figure 2 As shown, the present invention provides a high-performance stone plastic floor substrate, comprising the following components in parts by weight:
[0033] 300-400 parts of filler; 1-5 parts of coupling agent; 100 parts of PVC resin raw material; 5-15 parts of plasticizer; 5-15 parts of heat stabilizer; 0.2-2 parts of lubricant; 5-15 parts of heat stabilizer; 10-20 parts of modifier; wherein the filler comprises recycled marble powder and quartz powder, and the recycled marble powder adopts recycled marble waste powder.
[0034] Preferably, the coupling agent is an aluminate coupling agent.
[0035] Preferably, the PVC resin raw material consists of polyvinyl chloride resin with a degree of polymerization of 1250 to 981.
[0036] Preferably, the plasticizer is a compound of epoxidized soybean oil and dioctyl terephthalate.
[0037] Preferably, the heat stabilizer is a calcium-zinc composite stabilizer.
[0038] Preferably, the lubricant is at least one of calcium stearate, polyethylene wax and stearic acid.
[0039] Preferably, the modifier is a compound of two of acrylonitrile-butadiene-styrene plastic, chlorinated polyethylene and nitrile-butadiene rubber.
[0040] The present invention provides a method for preparing a high-performance stone plastic floor substrate as described above, comprising the following steps:
[0041] Step S1, mixing: pouring recycled marble powder, quartz powder, coupling agent, PVC resin raw material, plasticizer, heat stabilizer, lubricant, and modifier into a high-speed mixer in the order of powder first and liquid later to mix to obtain a substrate board material.
[0042] Wherein, step S1 specifically includes:
[0043] Step S11, surface modification: mixing the regenerated marble powder and the coupling agent at 100-110° C. in a high-speed mixer for 30 minutes to obtain modified regenerated marble powder;
[0044] Step S12, cooling: adding the modified regenerated marble powder into a low-speed mixer for cooling, and stirring until the temperature reaches room temperature;
[0045] Step S13, mixing: adding the modified regenerated marble powder cooled in step S12, quartz powder, PVC resin raw material, plasticizer, heat stabilizer, lubricant, and modifier into a high-speed mixer in the order of powder first and liquid later, mixing and drying to obtain a substrate board material.
[0046] Step S2, extrusion: the substrate plate material is squeezed into a mold through an extruder to form a semi-finished substrate plate.
[0047] Wherein, a thermostat is provided on the extruder in step S2 to set six temperature control zones, which are zone 1, zone 2, zone 3, zone 4, zone 5 and zone 6; wherein the temperature setting value of zone 1 is 150-155°C, the temperature setting value of zone 2 is 155-160°C, the temperature setting value of zone 3 is 160-170°C, the temperature setting value of zone 4 is 170-180°C, the temperature setting value of zone 5 is 180-190°C and the temperature setting value of zone 6 is 180-190°C;
[0048] The mold temperature in step S2 is 190-200° C., and eight zones are respectively provided.
[0049] Among them, the extruder is a SJZ92 / 188-2200 twin-screw extruder.
[0050] Among them, the screw speed of the twin-screw extruder is 20r / min.
[0051] Step S3, cooling and cutting: After the semi-finished substrate board is placed on a cooling device for cooling and shaping, cutting and trimming are performed according to product specifications to obtain a high-performance stone plastic floor substrate product. The product has a certain toughness, making it not easy to tear, high strength, good impact resistance, excellent shrinkage performance, and the raw materials used are also green and environmentally friendly materials, without environmental risks, and low cost.
[0052] Embodiment 1:
[0053] (1) 300 parts of recycled marble powder and 3 parts of aluminate coupling agent are added to a high-speed mixer at a temperature of 100-110°C for 30 minutes to obtain modified recycled marble powder. The modified recycled marble powder mixed in the high-speed mixer is then added to a low-speed mixer for cooling, stirred until room temperature, and then added to a high-speed mixer with 100 parts of polyvinyl chloride (PVC), 40 parts of quartz powder, 3 parts of epoxy soybean oil, 4 parts of dioctyl terephthalate, 5 parts of calcium zinc composite stabilizer, 0.5 parts of polyethylene wax, 0.3 parts of stearic acid, 10 parts of acrylonitrile-butadiene-styrene plastic (ABS), and 5 parts of chlorinated polyethylene in the order of powder first and liquid, mixed and dried at 60°C for 2 hours to obtain a substrate board material.
[0054] (2) The substrate material is then extruded through a twin-screw extruder and placed in a mold for molding to obtain a semi-finished substrate material.
[0055] Among them, the temperature setting value of zone one is 150-155°C, the temperature setting value of zone two is 155-160°C, the temperature setting value of zone three is 160-170°C, the temperature setting value of zone four is 170-180°C, the temperature setting value of zone five is 180-190°C and the temperature setting value of zone six is 180-190°C; during extrusion, the rotation speed is 20 / min and the temperature of the mold is 190-200°C.
[0056] (3) After the semi-finished substrate plate is placed on a cooling device and cooled to room temperature, it is cut into stone plastic plates with a length of 3000 mm and a width of 1500 mm by a cutting machine, and the edges are trimmed to obtain a molded product.
[0057] Comparative Example 1:
[0058] (1) 300 parts of recycled marble powder, 100 parts of polyvinyl chloride (PVC), 50 parts of quartz powder, 5 parts of epoxy soybean oil, 5 parts of dioctyl terephthalate, 8 parts of calcium zinc composite stabilizer, 0.5 parts of polyethylene wax, 0.3 parts of stearic acid, 15 parts of acrylonitrile-butadiene-styrene plastic (ABS), and 10 parts of chlorinated polyethylene are added into a high-speed mixer in the order of powder first and then liquid, mixed and dried at a drying temperature of 60° C. and a mixing time of 2 hours to obtain a substrate board material.
[0059] (2) The substrate material is then extruded through a twin-screw extruder and placed in a mold for molding to obtain a semi-finished substrate material.
[0060] Among them, the temperature setting value of zone one is 150-155°C, the temperature setting value of zone two is 155-160°C, the temperature setting value of zone three is 160-170°C, the temperature setting value of zone four is 170-180°C, the temperature setting value of zone five is 180-190°C and the temperature setting value of zone six is 180-190°C; during extrusion, the rotation speed is 20 / min and the temperature of the mold is 190-200°C.
[0061] (3) After the semi-finished substrate plate is placed on a cooling device and cooled to room temperature, it is cut into stone plastic plates with a length of 3000 mm and a width of 1500 mm by a cutting machine, and the edges are trimmed to obtain a molded product.
[0062] Comparative Example 2:
[0063] (1) 300 parts of recycled marble powder, 100 parts of polyvinyl chloride (PVC), 30 parts of quartz powder, 8 parts of epoxy soybean oil, 8 parts of dioctyl terephthalate, 8 parts of calcium zinc composite stabilizer, 1 part of polyethylene wax, 0.5 parts of stearic acid, 15 parts of acrylonitrile-butadiene-styrene plastic (ABS), and 15 parts of chlorinated polyethylene are added into a high-speed mixer in the order of powder first and then liquid, mixed and dried at a drying temperature of 60° C. and a mixing time of 2 hours to obtain a substrate board material.
[0064] (2) The substrate material is then extruded through a twin-screw extruder and placed in a mold for molding to obtain a semi-finished substrate material.
[0065] Among them, the temperature setting value of zone one is 150-155°C, the temperature setting value of zone two is 155-160°C, the temperature setting value of zone three is 160-170°C, the temperature setting value of zone four is 170-180°C, the temperature setting value of zone five is 180-190°C and the temperature setting value of zone six is 180-190°C; during extrusion, the rotation speed is 20 / min and the temperature of the mold is 190-200°C.
[0066] (3) After the semi-finished substrate plate is placed on a cooling device and cooled to room temperature, it is cut into stone plastic plates with a length of 3000 mm and a width of 1500 mm by a cutting machine, and the edges are trimmed to obtain a molded product.
[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high-performance stone plastic floor substrate, characterized in that: The composition comprises the following components in parts by weight: 300-400 parts of filler; 1-5 parts of coupling agent; 100 parts of PVC resin raw material; 5-15 parts of plasticizer; 5-15 parts of heat stabilizer; 0.2-2 parts of lubricant; 5-15 parts of heat stabilizer; 10-20 parts of modifier; wherein the filler includes recycled marble powder and quartz powder.
2. A high-performance stone plastic floor substrate according to claim 1, characterized in that , the coupling agent is an aluminate coupling agent.
3. A high-performance stone plastic floor substrate according to claim 1, characterized in that The PVC resin raw material is composed of polyvinyl chloride resin with a degree of polymerization of 1250 to 981.
4. A high-performance stone plastic floor substrate according to claim 1, characterized in that The plasticizer is a compound of epoxidized soybean oil and dioctyl terephthalate.
5. A high-performance stone plastic floor substrate according to claim 1, characterized in that , the heat stabilizer is a calcium-zinc composite stabilizer.
6. A high-performance stone plastic floor substrate according to claim 1, characterized in that , the lubricant is at least one of calcium stearate, polyethylene wax and stearic acid.
7. The high-performance stone plastic floor substrate according to claim 1 is characterized in that The modifier is compounded from two of acrylonitrile-butadiene-styrene plastic, chlorinated polyethylene and nitrile-butadiene rubber.
8. A method for preparing a high-performance stone plastic floor substrate according to any one of claims 1 to 7, characterized in that , including the following steps: Step S1, mixing: pouring recycled marble powder, quartz powder, coupling agent, PVC resin raw material, plasticizer, heat stabilizer, lubricant, and modifier into a high-speed mixer in the order of powder first and liquid second to obtain a substrate board material; Step S2, extrusion: extruding the substrate plate material into a mold through an extruder to obtain a semi-finished substrate plate; Step S3, cooling and cutting: placing the semi-finished substrate sheet on a cooling device to cool and shape it, and then cutting and trimming the edges to obtain a formed product.
9. The preparation method according to claim 8, characterized in that ,Step S1 specifically includes: Step S11, surface modification: mixing the regenerated marble powder and the coupling agent at 100-110° C. in a high-speed mixer for 30 minutes to obtain modified regenerated marble powder; Step S12, cooling: adding the modified regenerated marble powder into a low-speed mixer for cooling, and stirring until the temperature reaches room temperature; Step S13, mixing: adding the modified regenerated marble powder cooled in step S12, quartz powder, PVC resin raw material, plasticizer, heat stabilizer, lubricant, and modifier into a high-speed mixer in the order of powder first and liquid later, mixing and drying to obtain a substrate board material.
10. The preparation method according to claim 9, characterized in that , six temperature control zones are arranged on the extruder in step S2, and the six temperature control zones are zone 1, zone 2, zone 3, zone 4, zone 5, and zone 6; wherein the temperature setting value of zone 1 is 150-155°C, the temperature setting value of zone 2 is 155-160°C, the temperature setting value of zone 3 is 160-170°C, the temperature setting value of zone 4 is 170-180°C, the temperature setting value of zone 5 is 180-190°C, and the temperature setting value of zone 6 is 180-190°C; The mold temperature in step S2 is 190-200°C.